Finding and fixing vulnerabilities in information systems : the vulnerability assessment & mitigation methodology - Antón, Philip S. (Rand note ;, 2003)
Understanding an organization's reliance on information systems and how to mitigate the vulnerabilities of these systems can be an intimidating challenge--especially when considering less well-known weaknesses or even unknown vulnerabilities that have not yet been exploited. The authors, understanding the risks posed by new kinds of information security threats, build on previous RAND mitigation techniques by introducing the Vulnerability Assessment and Mitigation (VAM) methodology. The six-step procedure uses a top-down approach to protect against future threats and system failures while mitigating current and past threats and weaknesses. The authors lead evaluators through the procedure of classifying vulnerabilities in their systems' physical, cyber, human/social, and infrastructure elements, and identifying which security techniques can be relevant for these vulnerabilities. The authors also use VAM to break down information compromises into five fundamental components of attack or failure: knowledge, access, target vulnerability, non-retribution, and assessment. In addition, a new automated tool implemented as an Excel spreadsheet is discussed; this tool greatly simplifies using the methodology and emphasizes analysis on cautions, risks, and barriers.